Pengaruh Rasio Kecukupan Modal, Likuiditas, Risiko Kredit, dan Efisiensi Biaya Terhadap Kinerja Keuangan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia 2019-2021 - Shavania Febriekasari; Sri Sudarsi (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study uses the variables Capital Adequacy Ratio (CAR), Liquidity (LDR), Credit Risk (NPL), and Cost Efficiency (BOPO) as independent variables. The dependent variable used is Financial Performance (ROA). This study aimed to analyze the effect of independent variables of the Financial Performance (ROA). The population are all banking companies listed on the Indonesia Stock Exchange (IDX) 2019 - 2021. The data source from the Annual Financial Reports of banking companies listed on the IDX. The sample used in this study were 46 banking companies listed on the Indonesia Stock Exchange (IDX) with a purposive sampling techniques. Testing hypothesis in this study using multiple regression analysis (Multiple Regression) and the software used is IBM SPSS Statistics version 25. The results of the study after partial hypothesis test showed that the Capital Adequacy Ratio had significant positive effect on Financial Performance, Liquidity and Credit Risk had no significant effect on Financial Performance and Cost Efficiency had negative and significant effect Financial Performance.